1999
DOI: 10.1093/hmg/8.1.137
|View full text |Cite
|
Sign up to set email alerts
|

The human telomerase catalytic subunit hTERT: organization of the gene and characterization of the promoter

Abstract: Telomerase, the enzyme that synthesizes telomeric DNA, is not expressed in most human somatic cells but is activated with in vitro immortalization and during tumorigenesis, and repressed by cell differentiation. Of the two components of the core enzyme, the catalytic protein hTERT is limiting for activity. To investigate mechanisms of hTERT gene regulation, we have cloned genomic sequences encompassing the complete hTERT transcription unit. The hTERT gene consists of 16 exons and 15 introns spanning approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
348
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(362 citation statements)
references
References 28 publications
11
348
1
2
Order By: Relevance
“…The mechanisms by which the hTERT core promoter works so differentially in tumors and normal cells are still unclear. However, it has been reported that c-Myc, 29,[53][54][55][56][57] Sp1 57 and estrogen 58,59 activated hTERT promoter, but p53, 60 WT-1 61 and Mad1 62 were important factors for the Figure 10 Ad5/3hTERTE1 suppressed tumor growth in vivo. Intact SBC5 cells (1 Â 10 7 ) were injected s.c. into nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which the hTERT core promoter works so differentially in tumors and normal cells are still unclear. However, it has been reported that c-Myc, 29,[53][54][55][56][57] Sp1 57 and estrogen 58,59 activated hTERT promoter, but p53, 60 WT-1 61 and Mad1 62 were important factors for the Figure 10 Ad5/3hTERTE1 suppressed tumor growth in vivo. Intact SBC5 cells (1 Â 10 7 ) were injected s.c. into nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…TAK1 represses hTERT transcription T Fujiki et al in this repression are located in the first 164 bp of the hTERT promoter, which has been identified as the core promoter region essential for the transcriptional activation of the hTERT gene and contains several potential transcription factor-binding elements such as the GCbox and E-box (Figure 1b) (Cong et al, 1999;Horikawa et al, 1999;Takakura et al, 1999;Won et al, 2002).…”
Section: Tak1 Represses Htert Gene Transcriptionmentioning
confidence: 99%
“…The oncoprotein c-Myc was reported to activate the hTERT core promoter by binding to the E-boxes located at the promoter site (Cong et al, 1999;Horikawa et al, 1999). Further, the identified cis-elements also include the Sp1-binding sites (GC-boxes) at the core promoter that are crucial for the transactivation of the hTERT gene (Horikawa et al, 1999;Takakura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid pLacZ contains the cytomegalovirus (CMV) promoter-regulated LacZ gene 78 Plasmid pTLuc was generated by subcloning a 342 bp fragment of the hTERT promoter (À344 to À2 relative to the hTERT ATG) from plasmid P-344 79 upstream of the luciferase reporter gene in the pGL2-Basic vector (pGL2, Promega, Madison, WI, USA). Plasmid Tyrosinase-2, containing the tyrosinase promoter-regulated luciferase gene, 7 was kindly provided by Dr. David L. Bartlett (National Cancer Institute, Frederick, MD, USA).…”
Section: Plasmidsmentioning
confidence: 99%